Sustainability Report and Company Value: The Effect of Moderation on Intellectual Capital (Empirical Study of Mining Companies Listed on the Indonesian Stock Exchange 2018-2023) - Nurafni Ansar; Linda Arisanty Razak; Wa Ode Rayyani (IECON: International Economics and Business Conference, 2024)
This study aims to test the effect of sustainability reports on company value and test intellectual capital moderating the effect of sustainability reports on company value in the mining sector listed on the Indonesia Stock Exchange (2024) in 2018-2024. This study uses a quantitative method, the sample in this study was 10 companies with 6 years in the mining sector. This research data was obtained using secondary data. The results of the study from the data processed using SPSS 26 statistical calculations, Based on the partial output results of SPSS 26, the results of the study of the Sustainability report variable have a significant positive effect on company value, a good sustainability report usually provides information about the company's social and environmental responsibility, which can increase investor confidence and other stakeholders and the intellectual capital variable that moderates the sustainability report also has a significant positive effect on company value. High intellectual capital can strengthen the positive impact of sustainability reports on company value, because companies that have strong intellectual capital tend to be better able to implement and communicate sustainability initiatives effectively. Overall, this study shows that sustainability reporting has a positive impact on firm value and that intellectual capital can enhance the strength of this impact in the context of mining companies listed in the mining sector of the Indonesia Stock Exchange (IDX).